Pathogenic Variants in GALC Gene Correlate With Late Onset Krabbe Disease and Vision Loss: Case Series and Review of Literature - Bascou, Nicholas A.; Beltran-Quintero, Maria L.; Escolar, Maria L. (Frontiers in Neurology, 2020)
Background: Krabbe disease is an autosomal recessive demyelinating disorder resulting from deficiency of the lysosomal enzyme galactocerebrosidase. While blindness is often described as a characteristic finding of the disease, it is more common in the infantile phenotype, where vision loss typically arises in the late stages of disease. In comparison, reports of vision loss in late onset phenotypes are less well described and may be subject to variation between genotypes. Methods: Charts of Krabbe patients with a confirmed diagnosis, who presented with substantial visual impairment, were retrospectively reviewed from a larger group of 199 Krabbe patients. Assessment of clinical status was obtained through review of neurological evaluations, neurodevelopmental assessments, ophthalmological evaluations, visual evoked potentials (VEP), electroretinogram (ERG), nerve conduction velocity (NCV) studies, auditory brainstem responses (ABR), and brain magnetic resonance imaging (MRI), Results: Five late onset patients with Krabbe disease (four juvenile and one late-infantile) were included. Three patients were homozygous for c.956A>G_p.Y319C, one was compound heterozygous for c.296+1G>T and c.956A>G_p.Y319C, and one was compound heterozygous for c.1186C>T_p.R396W and c.1901T>C_p.L634S. All patients were of Asian descent and presented initially with vision impairment. Notably, the patients did not present with marked appendicular spasticity or axial hypotonia and all five reached developmental milestones within the normal time frame. For neurophysiological testing, no patient showed abnormalities in NCV or ABR. However, abnormalities in VEP or ERG were seen in all patients. The one patient who underwent transplantation stabilized following treatment. Conclusions: Depending on their genotype, patients with late onset Krabbe disease may initially present with vision loss. Furthermore, patients with p.L634S and p.Y319C should be closely monitored for changes in vision and VEP. This knowledge will become increasingly important as physicians may otherwise overlook these signs and symptoms when monitoring children identified through newborn screening who have the variants described in this report.